Application of Behavior Contract Group Counseling to Improve Discipline among High School Students - Lailatus Sa’adah; Nurudducha Nurudducha (Indonesian Journal of Guidance and Counseling Studies, 2025)
Background: Tardiness remains a disciplinary problem that disrupts the learning process in many secondary schools. Behavior-based interventions are needed to ensure measurable and sustainable change. Objective: To assess the effectiveness of group counseling using behavioral contract techniques in reducing undisciplined behavior (tardiness) among students at SMA Negeri 18 Surabaya. Method: A two-cycle qualitative classroom action research, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects consisted of four students with a history of tardiness, 7–13 times per month. Data were collected through observation, interviews, and documentation of tardiness records and analyzed descriptively. Result: After Cycle I, the frequency of tardiness decreased to 2–3 times per week. In Cycle II, tardiness was no longer found, along with the strengthening of student commitment to the agreed behavior contract and stricter monitoring. Conclusion: Group counseling using behavior contract techniques is effective in reducing tardiness at SMA Negeri 18 Surabaya and is suitable for integration into the school's guidance and counseling program. Contribution: This study adds to the applied evidence of behavioral counseling on the issue of punctuality by providing replicable implementation components (contract format, reinforcement and consequence schemes, and monitoring mechanisms), while also providing a two-cycle action research framework that guidance counselors can adopt in a high school context.